Anatomical Characterization of Thermosensory AC Neurons in the Adult Drosophila Brain. - Shih, H.W.; Chiang, A.S. (Journal of Neurogenetics, 2011)
Temperature preference is vital for the survival of all animals. A small set of warm-activated anterior cell (AC) neurons acting as an internal thermosensor in the Drosophila brain is critical for optimal temperature selection ( Hamada et al., 2008 , Nature, 454, 217-220). Here, the authors analyze the circuit components of the AC neurons by characterization of its spatial distribution, dendrite-axon polarity, and the putative type of neurontransmitter released. The results show that the AC neurons are serotonergic, do not have any dendrites, and send axons bilaterally to the superior dorsofrontal protocerebrum (SDFP). Searching the FlyCircuit database for neurons with serotonin receptor and dendrites in the SDFP, the authors found a dorsal-anterior-lateral (DAL) neuron as a candidate postsynaptic partner of the AC neurons. In conclusion, by morphological analysis of the AC neurons, the authors show a general strategy for predicting brain circuits orchestrating thermosensory behaviors.